Discrimination Against Negroes in the Administration of Criminal Law in Missouri - Jules B. Gerard; T. Rankin Terry Jr. (Washington University Law Quarterly, 1970)
This Article is a preliminary effort to determine whether it is possible to evaluate some of the charges of subtle discrimination against Negroes in the administration of criminal law.
Keywords: Administration of justice; Discrimination; Race